Exploring teachers' career self-management. Considering the roles of organizational career management, occupational self-efficacy, and learning goal orientation. Issue 4 (8th August 2019) - Runhaar, Piety; Bouwmans, Machiel; Vermeulen, Marjan
ABSTRACT: The current study examines how organizational career management – i.e. activities undertaken by schools in order to plan and manage teachers' careers – relates to teachers' career self-management – i.e. teachers steering their careers by means of searching for opportunities, networking, or seeking supervisory support. Moreover, it examines the mediating roles of occupational self-efficacy and learning goal orientation in this relationship. Mediation analysis in SPSS, using the PROCESS macro of survey data from 220 Dutch secondary school teachers, showed that positive relationships between organizational career management and career self-management were mediated by occupational self-efficacy and learning goal orientation.